Expressão gênica, localização espaço-temporal e atividade antifúngica de proteínas ligantes à quitina durante o desenvolvimento e germinação da semente de Moringa oleifera - Garcia, Tarcymara Barata (2018)
Seeds accumulate great amounts of proteins that are used as source of carbon, nitrogen, sulfur, and amino acids required during the initial development stages of plants. The 2S albumin family encompasses storage proteins that in addition have other activities like inhibition of proteolytic enzymes and antibacterial and antifungal compounds. Due its biological properties, 2S albumins stand out for their potential to combat plant diseases in economically important crops. In place of commercial compounds that are costly and cause environmental pollution. Aware of these problems, our research group has been investigating the chitin binding proteins purified from Moringa oleifera quiescent seeds (Mo-CBPs) that also belong to the 2S albumins family. Mo-CBPs present a potent activity against phytopathogenic fungi. The present work aims to assess the gene expression, spatio-temporal localization and possible antifungal activity of Mo-CBPs during Moringa oleifera seed development and germination. During M. oleifera seed maturation, four stages of development, counted in days after anthesis (DAA), were studied: globular embryo (15DAA); heart-shaped embryo (30 DAA); cotyledonary embryo prior dissection (60 DAA); and cotyledonary embryo after dissection (90 DAA). Accumulation of Mo-CBPs transcripts and corresponding proteins were not detected in the initial stages of embryonic development (15 and 30 DAA). However, their transcripts were intensely expressed in the final seed maturation stages, particularly at 60 DAA. The presence of Mo-CBPs assessed by ELISA was detected only in the last stages of seed maturation (60 and 90 DAA). Mo-CBPs in situ localization analyses showed their strong presence into vacuolar structures in the cotyledons of mature seeds (90 DAA). During germination, immunohistochemistry analyses revealed a degradation pattern of Mo-CBPs. Antifungal activity assay indicated that Mo-CBPs are active in the last stages of seed maturation. They inhibited the spore germination of three Fusarium species. All together, these results are similar to data obtained for other 2S albumins belonging to Brassicales. These results also suggest that Mo-CBPs play a dual role as storage and defense proteins in the seeds of M. oleifera.